Rancang Alat Pengukur Tinggi Badan Dengan Output Suara Berbasis Arduino Uno - Yandri Lesmana Yandri Lesmana; Iwan Purnama; Rohani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
In every health test, of course, there is a measurement of height, so that a person's height can be measured, starting from the soles of the feet to the head, the height measuring device used is still manual, which uses a meter and the measurement process in done by someone to measure the height of someone who wants to know his height so that the results of these measurements require more time when the number of people measured is more than 20 people in other words the manual height meter is less effective when used during the recruitment period of new employees started. With these constraints, the authors created a tool that can measure height automatically by utilizing an Ultrasonic sensor as a measuring tool and an Arduino Uno microcontroller as a control center by displaying measurement results on a 16x2 LCD screen. In this result it can replace the manual height measuring device so that it helps the activities of workers in carrying out their noble duties to provide health services to the general public.